2018
DOI: 10.1016/j.ultsonch.2018.03.018
|View full text |Cite|
|
Sign up to set email alerts
|

Wastewater treatment for Amoxicillin removal using magnetic adsorbent synthesized by ultrasound process

Abstract: In this study, the effect of magnetic adsorbent prepared from Olive kernel (MA-OK) was studied in the Amoxicillin (AMX) removal. The synthesized adsorbent, under a sonochemical method, were characterized using Field emission scanning electron microscope (FESEM), Fourier transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET) and X-ray diffraction (XRD). The absorption functions in the batch experiments were studied using the expected parameters for the maximum absorption capacities (q) such as pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…According to the pseudo-second-order rate constant, the fastest adsorbing compound is ciprofloxacin followed by amoxicillin, penicillin-G, and doxycycline; respectively. The reported rate constants are broadly consistent with those reported for the same antibiotics 59,61,69,70 . The pseudo-second order kinetic model suggests that chemical adsorption is the dominant mechanism, involving electrostatic attraction, which is consistent with the variable pH experiments presented in the coming section.…”
Section: Adsorption Kineticssupporting
confidence: 86%
See 1 more Smart Citation
“…According to the pseudo-second-order rate constant, the fastest adsorbing compound is ciprofloxacin followed by amoxicillin, penicillin-G, and doxycycline; respectively. The reported rate constants are broadly consistent with those reported for the same antibiotics 59,61,69,70 . The pseudo-second order kinetic model suggests that chemical adsorption is the dominant mechanism, involving electrostatic attraction, which is consistent with the variable pH experiments presented in the coming section.…”
Section: Adsorption Kineticssupporting
confidence: 86%
“…On the other hand, doxycycline and ciprofloxacin are well-described by both adsorption mechanisms. Previous studies have shown that both adsorption mechanisms could coexist in the same adsorption system 58,61 . Thus, the variations encountered in modeling the adsorption of the studied antibiotics is attributed to their chemical nature and their affinity for adsorption onto PIM-1.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained data show that the R 2 value is higher for the PSO model for both adsorbents (0.9416 for OSBC and 0.9224 for MAG-OSBC). These findings indicate that the rate of the adsorption reaction depends on both drug and adsorbent and that the reaction could be represented as follows, Equation ( 12 In agreement with the literature, and as is shown in Table 1, the adsorption of PhACs and other organics on adsorbents derived from the olive stones followed a PSO kinetic model [31][32][33][34][35]37].…”
Section: Kinetic Studiessupporting
confidence: 83%
“…This finding shows that the MAG-OSBC as an adsorbent possesses a higher adsorptive capability for CLOF, and this behavior could be related to the higher surface area and pore volume compared to the pristine OSBC. Studies using zinc chloride-activated carbon prepared from olive stone (ACOS), magnetic adsorbent from the olive kernel (MA-OK), and olive stones chemically activated with phosphoric acid showed that Langmuir isotherm could best describe the adsorption of the investigated organic pollutants [33,35,36]. The obtained data show that the performance of the current adsorbents is comparable to the conventional adsorbents.…”
Section: Adsorption Isothermsmentioning
confidence: 89%
See 1 more Smart Citation